3‐Alkenyltyrosines Accessed by Suzuki–Miyaura Coupling: A Key Intermediate in the Synthesis and Mechanistic Study of Povarov Multicomponent Reactions. Issue 7 (1st June 2017) - Vasconcelos, Stanley N. S.; Menezes da Silva, Vitor H.; Braga, Ataualpa A. C.; Shamim, Anwar; Souza, Frederico B.; Pimenta, Daniel C.; Stefani, Hélio A.
Abstract: 3‐Vinyl and 3‐stilbenyl tyrosine derivatives, accessed by the Suzuki–Miyaura coupling reaction in good yields, are presented. These synthetic olefins then provided a fast and effective synthesis of functionalized quinolines by a silver‐catalyzed, microwave‐mediated Povarov reaction in just 40 min. In addition, we demonstrate a tandem one‐pot microwave‐mediated Povarov–CuAAC (copper‐catalyzed azide–alkyne cycloaddition) synthesis to provide a 1, 2, 3‐triazole ring with 35 % overall yield. We propose a Povarov/aromatization mechanism, based on high‐resolution mass spectrometry experiments, combined with computational studies based on density functional theory (DFT) methods. Abstract : Fast functionalized quinolines : An unprecedented synthesis of 4‐tyrosilquinoline‐2‐carboxylates by a silver catalyzed, microwave‐mediated Povarov reaction from a Suzuki–Miyaura cross‐coupling product is reported. A plausible Povarov/aromatization mechanism is proposed, based on high‐resolution mass spectrometry experiments, combined with computational studies based on density functional theory (DFT) methods.